Assessing the Factors Influencing Attrition of Health Workers in Government Health Units in Lyantonde District, Uganda. - Kansiime, Benon (Kabale University, 2023)
Introduction The shortage of health workers remains a critical public health issue globally despite of national strategic plans enacted in 2014 by world leaders which aimed at handling the shortage of health workforce. This study assessed the factors influencing attrition of health workers in government health units in Lyantonde district, Uganda. This was guided by three specific objectives of the study which were to: find out the drivers of attrition of health workers in Lyantonde district; determine the effects of attrition of health workers in Lyantonde district; and establish retention measures of health workers in Lyantonde district. Methodology Across sectional study of collecting qualitative and quantitative data was conducted on 171 study participants including health workers, Chief Administrative Officer, the District Health Officer, the District Principal Human Resource Officer, Secretary District Service Commission, the Chairperson District Service Commission, the District Principal Internal Auditor, and Secretary for Health, Medical superintendent Lyantonde Hospital, District Planner and the Chief Finance Officer. Frequencies, percentages, means, standard deviations and correlations were used to achieve the objectives. Thematic analysis was used to analyse the qualitative data. Results 171 respondents participated in the study making a response rate of 95%, 34.5% were males, and 65.5% were females. The cadre distribution of the participants was as follows: Medical Officers 5 (2.9%), clinical officers 14 (8.2%), Nursing 82 (48.0%), Health Assistant 11(6.4%), Health inspector 4 (2.3), Radiographers 2 (1.2), Laboratory Assistants 9 (5.3%), Laboratory technicians 3(1.8%), Dispensers 2 (1.2%), Orthopaedic officer 1 (0 .6%), and Midwives 38 (22.2%). The drivers of attrition included: low pay/salary/allowances 49.7%, limited opportunities for promotion 51.5%, poor/lack of utilities 62.6%, lack of housing facilities 75.4%, and poor education facilities for health workers 48.5%. the effect of attrition of health workers included; shortage of health workers 85.5%, lack of access to all health services in the facilities 73.1%, and poor service delivery 43.3%. Moreover, on measures to mitigate the attrition of health workers, the following were found to be most important: provision of accommodation to the health workers (Mean=4.02), the government should provide training and promotion outlets (Mean=4.08), provision of incentives (Mean=4.31), provision of retention allowances (Mean=4.16). However, respondents were not sure if good relationship between the community and the health workers can lead to retention (Mean=3.0), and Availability of infrastructure and quality services (Mean=3.82). Discussion: The majority of the health workers have enough experience by they still face challenges of: inadequate pay, lack of equipment, health units accessibility, and availability of housing and social amenities which may contribute to their attrition. The effects of attrition of health workers cited in the study were: shortage of health workers, inadequate service provision, and patients did not access all services. Measures to mitigate the attrition of health workers cited in the study were provision of accommodation to health workers, training and promotion outlets for health workers with additional qualifications, provision of retention allowances especially to those working in the hard to reach areas.